Application of Production-oriented Approach in College Integrated English Teaching -under the Background of Curriculum Ideological and Political Education - Ma, Shuning (Pacific International Journal, 2024)
The Production-Oriented Approach, a foreign language teaching method with Chinese characteristics founded by Wen Qiufang, has been developed over the past decade with the goal of enhancing the quality of English instruction in higher education settings across China. This paper aims to apply this theory to the teaching framework of ideological and political education within integrated English courses and subsequently evaluate its effectiveness.A specific case study, centered on the text “Spring Sowing” from a Contemporary College English Reading course, demonstrates the practical implementation of ideological and political education using the POA. The paper describes the teaching design of this unit within the POA framework, encompassing the motivating, enabling, and assessing stages. Additionally, students’ feedback following the implementation of this teaching approach highlights its positive impact on linguistic advancement, thematic comprehension, and appreciation for farmer-related themes.The study’s findings demonstrate that a college integrated English course based on the POA seamlessly integrates language knowledge with ideological and political elements, resulting in a noticeable enhancement in teaching quality and efficacy. It demonstrates the feasibility and effectiveness of incorporating ideological and political education within English language instruction using the POA framework, offering valuable insights for future curriculum development and implementation in Chinese higher education.